Scaling Behavior and Phases of Nonlinear Sigma Model on Real Stiefel Manifolds Near Two Dimensions - Gavrilik, Alexandre; Nazarenko, Andriy (Universe, 2025)
For a quasi-two-dimensional nonlinear sigma model on the real Stiefel manifolds with a generalized (anisotropic) metric, the equations of a two-charge renormalization group (RG) for the homothety and anisotropy of the metric as effective couplings are obtained in a one-loop approximation. Normal coordinates and the curvature tensor are exploited for the renormalization of the metric. The RG trajectories are investigated and the presence of a fixed point common to four critical lines or four phases (tetracritical point) in the general case, or its absence in the case of an Abelian structure group, is established. For the tetracritical point, the critical exponents are evaluated and compared with those known earlier for a simpler particular case.
Keywords: nonlinear sigma model; Stiefel manifold; RG beta functions; tetracritical point; critical exponents; universality classes